DESIGN OF PLUMBING SYSTEM AT TUNJUNGAN PLAZA APARTMENT, SURABAYA - Sarah Meilani; Ariani Dwi Astuti; Ratnaningsih Ratnaningsih (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2017)
Aim: This study of plumbing system plan is  aimed at planning a plumbing system that is compatible with clean water, waste water and rain water management at Tunjungan Plaza apartment, Surabaya City, Indonesia according to SNI 8153-2015, and meet 5 aspects of safety, security, simplicity, beauty, and economy.  It applies water supply system which commonly used for tall buildings, namely Roof Tank system. Methodology and Result: Plumbing system planning methods are collecting and analyzing fluctuation in water use, planning clean water and recycled water systems by endorsing alternative piping for clean water and recycled water. In addition to water supply, recycled water system that utilizes waste water to be recycled for flushing closets and watering plants also required to be implemented. Average daily water consumption is 268 m3/day for clean water and 44 m3/day for recycled water with the capacity of ground water tank for clean water is 564.54 m3 and recycled water is 62 m3. Conclusion, significance and impact study: Clean water supply system will implement roof tank system and recycled water will reutilize wastewater for flushing on toilet tank and watering the plants. Waste water use separated system between grey water and black water and then distributed to STP to be treated and reused for flushing water closet and watering plants. Rain water goes to infiltration well by gravity through designed 1 well. Total amount of investment of plumbing equipment is Rp 2,157,697,501,- with cost of water supply per unit Rp 4,445,643,- meanwhile waste water piping cost per units is Rp 1,070,711,-.